The Role Supply Chain Management and Religiosity of Local Parliament Members against Fraud Rejection in Public Budgeting - Zamzam, Irfan; P. E. Saerang, David; Karamoy, Herman; B. Maramis, Joubert (International Journal of Supply Chain Management, 2020)
The purpose of this research is to investigate the relationship between religiosity, supply chain management, and the rejection of fraud in budgeting to the regional government with the moderating effect of the leadership. The research finding was based on quantitative methods by means of questionnaire while PLS-SEM has been used for analysis. The results showed that the higher the level of religiosity of local parliament members, the higher the attitude of rejection of fraud in regional budgeting. The results also showed that the higher the level of supply chain management, the higher the attitude of rejection of fraud in regional budgeting. The results highlight that individuals who have a level of religiosity in themselves will practice religious values by obeying the rules and carrying out obligations and being able to control themselves from all forms of fraud including fraud in the budgeting process. The results also exposed the leadership moderates the links among the religiosity, supply chain management, and the rejection of fraud in budgeting to the regional government.